Análisis de bentonitas de Ignacio Escudero, por expansión, rayos X y microscopía electrónica - Zamora Nevado, Roberto Martín (2022)
The bentonite analyzed comes from Cerro Mocho, district of Ignacio Escudero, province of Sullana, whose UTM coordinates are 9468762 (N) and 508203.00 (E), zone 17; corresponding to quadrangle 10b of the national geological map.  The expansive soils constitute a recurrent problem from the geotechnical point of view for the structures that are built on them; due to their composition rich in montmorillonite {Ca0.2(Al,Mg)2Si4O10(OH)2.xH2O}, which belongs to the smectite group; bentonites, when in contact with water, react increasing their volume, being representative of the most expansive clays; their use as experimental material for the simulation of this type of complex soils is ideal; it is therefore important an analysis that involves the knowledge of their physical and chemical properties and their mineralogical composition that influences this expansive behavior. The procedures carried out consisted of subjecting the bentonite to free expansion tests whose result determined a 47.5% swelling; and with the support of INGEMMET, an x-ray diffraction analysis (DRX) was carried out, which evidenced a mineralogical composition of montmorillonite in 37. 78%; and a scanning electron microscopy (SEM) analysis whose results showed aggregates of montmorillonite microcrystals with lamellar, wrinkled and leafy morphologies, glomerular microfabrics and stacked flakes, with sizes ranging from 2 to 10 µm on average. By sectors the sample presents in smaller proportion microcrystals of quartz, halite, carbonates, plagioclase, and ferromagnesian minerals.